Cauda Equina Enhancement in Wernicke Encephalopathy: An Atypical Radiologic Manifestation - Yadav, Ratan Pal; Mack, Meghan Lou; Subramanian, Subramanian (Indian Journal of Radiology and Imaging, 2025)
A 13-year-old female with restrictive eating and associated weight loss presented with progressive neurological decline, including bilateral ptosis, gait disturbance, dysphonia, and hyporeflexia. Brain magnetic resonance imaging revealed T2 and FLAIR (fluid-attenuated inversion recovery) hyperintensities in the medial thalami, periaqueductal gray matter, and mild diffuse cerebral and cerebellar volume loss characteristic of Wernicke encephalopathy (WE). Additionally, smooth enhancement of the cauda equina nerve roots was observed, a finding not usually seen in thiamine (vitamin B1) deficiency. Infectious, metabolic, and autoimmune causes were ruled out, and low serum thiamine levels established WE. This case highlights an atypical radiologic feature of WE—cauda equina enhancement, suggesting broader neurological involvement. Early diagnosis and thiamine repletion therapy are required immediately to prevent long-term neurological damage.
Keywords: Wernicke encephalopathy; thiamine deficiency; cauda equina enhancement